Impact of inhibitor development on treatment and quality of life of patients with hemophilia: a literature review (Research, Society and Development, 2022)
Hemophilia is an inherited bleeding disease and one of the main challenges of its treatment is the development of inhibitors. This work aimed to discuss the literature dealing with the presence of inhibitors given the diagnostic approach, therapy, and impact on quality of life. This is a review study consisting of 81 articles, the descriptors "Hemophilia" and "Coagulation Factor Inhibitors" were used. It is concluded that the development of inhibitors reflects the interaction between several factors such as genetic mutation, immune response, modulators, as well as acquired alterations. It implies an important challenge in the therapeutic scenario and impacts the quality of life of hemophilia patients.